Nutritional Risk Index Predicts Survival in Patients With Breast Cancer Treated With Neoadjuvant Chemotherapy - Chen, Li; Qi, Yihang; Kong, Xiangyi; Su, Zhaohui; Wang, Zhongzhao; Wang, Xiangyu; Du, Yaying; Fang, Yi; Li, Xingrui; Wang, Jing (Frontiers in Nutrition, 2022)
Nutritional risk index (NRI) is an index based on ideal body weight that aims to present body weight and serum albumin levels. It has been utilized to discriminate patients at risk of postoperative complications and predict the postoperative outcome of major surgeries. However, this index remains limited for breast cancer patients treated with neoadjuvant chemotherapy (NACT). The research explores the clinical and prognostic significance of NRI in breast cancer patients. This study included 785 breast cancer patients (477 cases received NACT and 308 cases did not) were enrolled in this retrospective study. The optimal NRI cutoff value was evaluated by receiver operating characteristic (ROC) curve, then reclassified as low NRI group (＜112) and high NRI group (≥112). The results demonstrated that NRI independently predicted survival on disease-free survival (DFS) and overall survival (OS) by univariate and multivariate Cox regression survival analyses (P=0.019, hazard ratio [HR]:1.521, 95%CI:1.071-2.161 and P=0.004, HR:1.415, 95%CI: 1.119-1.789; and P=0.026, HR:1.500, 95%CI:1.051-2.143 and P＜0.001, HR:1.547, 95% CI:1.221-1.959). According to the optimal cutoff value of NRI, the high NRI value patients had longer mean DFS and OS time in contrast to those with low NRI value patients (63.47 vs 40.50 months; 71.50 vs 56.39 months). Furthermore, the results demonstrated that the high NRI score patients had significantly longer mean DFS and OS time than those with low NRI score patients in early-stage breast cancer (χ2=9.0510, P=0.0026 and χ2=9.2140, P=0.0024) and advanced breast cancer (χ2=6.2500, P=0.0124 and χ2=5.8880, P=0.0152). The mean DFS and OS values in patients with high NRI scores were significantly longer in contrast to those with low NRI scores in different molecular subtypes. The common toxicities after NACT were hematologic and gastrointestinal reactions, and the NRI had no statistically significant effects on toxicities, except in nausea (χ2=9.2413, P=0.0024), mouth ulcers (χ2=4.8133, P=0.0282), anemia (χ2=8.5441, P=0.0140), and leukopenia (χ2=11.0951, P=0.0039). NRI serves as a minimally invasive, easily accessible and convenient prognostic tool for evaluating breast cancer prognoses and treatment efficacy, and may help doctors in terms of selecting measures of greater efficiency or appropriateness to better treat breast cancer.